Serovalue of hydatid disease in Baghdad - Abdul Rasool, Yousif A.; AL-Taie, Lazem H.; Husain, Haider A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Echinococcus granulosus is a one major species of medical and public health importance which causes cystic echinococcosis.Hydatid disease is able to modulate antiparasite immune responses, persist and flourish in humans. Objective: The main objective of this study is to diagnostic value for hydatidosis and to identify the prevalence in human in two different areas of Baghdad city which include urban and rural areas. Evaluating hydatid fluid antigen and hydatid cyst wall antigen for diagnosis of cystic echinococcosis(CE). preparation ELISA kit for detecting specific antibodies in patients and relative sera is considered as an important step in determining the recurrent case after surgical operation. Patients and Methods: Fifty patients infected with hydatidosis , One-hundred and seven relatives’ patients and Thirty patients’ follow-up. NAJAT-enzyme-linked immunosorbent assay(ELISA) and NAJAT-latex test for the Immunodiagnosis of cystic echinococcosis of human hydatid disease by detecting the specific antibodies in patients. Results: hydatidosis in females was the same as in the males. One-hundred and seven relatives’ patients. In rural area the seroprevalence were 12 male cases and 4 female cases ,While in urban area 5male cases,5 female cases,respectively. Thirty patients’ follow-up four patients developed recurrences at 3-7 months postoperatively. Conclusion: In relatives’ patients no statistically significant differences in the frequency between both sexes. But a highly statistically significant differences (p=0.05) were shown between hydatidosis infected persons in relation to area(urban area,rural area). There were no significant differences in the rates seropositive case for different occupations(p=0.05). NAJAT-enzyme-linked immunosorbent assay(ELISA) and NAJAT-latex test appeared to be a useful confirmatory tests with specific antigens represent good candidates for the Immunodiagnosis of cystic echinococcosis of human hydatid disease by detecting the specific antibodies in patients.